A human cell model for dynamic testing of MR contrast agents. (February 2011) - Aulanier, Anne-Lise; Doiron, Amber L.; Shepherd, Robert D.; Rinker, Kristina D.; Frayne, Richard; Andersen, Linda B.
To determine the initial feasibility of using magnetic resonance (MR) imaging to detect early atherosclerosis, we investigated inflammatory cells labeled with a positive contrast agent in an endothelial cell–based testing system. The human monocytic cell line THP-1 was labeled by overnight incubation with a gadolinium colloid (Gado CELLTrack) prior to determination of the in vitro release profile from T1-weighted MR images. Next, MR signals arising from both a synthetic model of THP-1/human umbilical vein endothelial cell (HUVEC) accumulation and the dynamic adhesion of THP-1 cells to activated HUVECs under flow were obtained. THP-1 cells were found to be successfully—but not optimally—labeled with gadolinium colloid, and MR images demonstrated increased signal from labeled cells in both the synthetic and dynamic THP-1/HUVEC models. The observed THP-1 contrast release profile was rapid, suggesting the need for an agent that is optimized for retention in the target cells for use in further studies. Detection of labeled THP-1 cells was accomplished with no signal enhancement from unlabeled cells. These achievements demonstrate the feasibility of targeting early atherosclerosis with MR imaging, and suggest that using an in vitro system like the one described provides a rapid, efficient, and cost-effective way to support the development and evaluation of novel MR contrast agents.